Heritability of running economy: a study made on twin brothers - Rodas, G.; Calvo, M.; Estruch, A.; Garrido, E.; Ercilla, G.; Areas, A.; Segura, R.; Ventura, J. L. (European Journal of Applied Physiology, 1998)
We did not detect a genetic component in RE (running economy) or in maximal oxygen uptake, but a genetic component for markers of anaerobic metabolism was present.